Bibliometric Analysis in Mapping Research with the Central Theme of Digital Content Marketing - Ulya Hasasi, Shina; Panca Rani, Meiliana; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
This research examines the development and trends of Digital Content Marketing (DCM) as a strategy to build better relationships with customers. We analyzed data from international journals published between 1988 and 2025 through a bibliometric approach, covering various elements such as digital transformation, social media, and consumer social learning. The bibliometric visualization revealed that